Relationship Between Madrasah Head Leadership and Teacher's Participation with Quality of Madrasah Tsanawiyah State District, Labuhan Batu District - Chairunnisa; Syarbaini Saleh (Britain International for Academic Research (BIAR) Publisher, 2019)
The research method uses correlation research, which is research that seeks to see the relationship between variables. The study population was all MTs teachers in Labuhan Batu District totaling 83 people. The sample was taken using proportional random sampling technique, so that the sample was taken as many as 75 people. The instrument used was a questionnaire, data analysis techniques were carried out with data descriptions, and hypothesis testing using simple regression and multiple regression. After the research data were analyzed, the following results were obtained: 1) There was a positive and significant relationship between the leadership of the madrasah head (X1) and the madrasah quality (Y) at Madrasah Tsanawiyah Labuhan Batu with moderate correlation levels with the correlation coefficient value of 0.092. While the value of the strength of the relationship that occurs between the two variables is 0.092 or 8%. 2) There is a positive and significant relationship between teacher's work participation (X2) and the quality of madrasah (Y) in Laban Batu Madrasah Tsanawiyah with moderate correlation levels with the correlation coefficient value of 0.390. While the value of the strength of the relationship that occurs between the two variables is 0.390 or 15.2%. 3) There is a positive and significant relationship between madrasah head leadership (X1) and teacher work participation (X2) with madrasah quality (Y) in Laban Batu Tsanawiyah Madrasah with moderate correlation levels with a correlation coefficient value of 0.512. While the value of the strength of the relationship that occurs between the two variables is 0.512 or 26.2%. The two independent variables go hand in hand with the dependent variable, meaning that the better the madrasa head leadership and teacher work participation, the better the madrasah quality.